Building An Ideal Library: Managing Funding And Improving Library Services In Schools: - sari, Yunita Kumala Sari; Ach. Zahri NA; Ali Nurhadi (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2025)
Effective financial management is a crucial factor in providing adequate facilities and quality services. Library management and library services play a crucial role in supporting the learning process and improving literacy at SMAN 1 Galis Pamekasan. This study aims to describe the implementation of library management, which also encompasses the funding aspect of facilities, including the planning, organization, implementation, and evaluation stages of services, as well as assessing the quality of services received by users. The findings indicate that planning is carried out through the procurement and grouping of book collections, while organization involves collaboration between the principal, treasurer, facilities and infrastructure officers, and librarians in meeting library facility needs. This involves collaboration between elements within the school environment to meet facility needs and manage library financing, although the funding mechanism applied is not yet optimal and has not been documented in detail. Service implementation includes borrowing and returning books based on student cards, cataloging collections, and regular literacy programs such as reading corners and writing competitions. The evaluation indicates challenges in student discipline and adaptation to information technology, particularly the use of e-books. Therefore, strengthening collaborative and innovative management is needed to improve service effectiveness and foster a culture of digital literacy among students.